Two novel protein-tyrosine kinases, each with a second phosphotransferase-related catalytic domain, define a new class of protein kinase. - Wilks, A F (1991)
The protein-tyrosine kinases (PTKs) are a burgeoning family of proteins, each of which bears a conserved domain of 250 to 300 amino acids capable of phosphorylating substrate proteins on tyrosine residues. We recently exploited the existence of two highly conserved sequence elements within the catalytic domain to generate PTK-specific degenerate oligonucleotide primers (A. F. Wilks, Proc. Natl. Acad. Sci. USA 86:1603-1607, 1989). By application of the polymerase chain reaction, portions of the catalytic domains of several novel PTKs were amplified. We describe here the primary sequence of one of these new PTKs, JAK1 (from Janus kinase), a member of a new class of PTK characterized by the presence of a second phosphotransferase-related domain immediately N terminal to the PTK domain. The second phosphotransferase domain bears all the hallmarks of a protein kinase, although its structure differs significantly from that of the PTK and threonine/serine kinase family members. A second member of this family (JAK2) has been partially characterized and exhibits a similar array of kinase-related domains. JAK1 is a large, widely expressed membrane-associated phosphoprotein of approximately 130,000 Da. The PTK activity of JAK1 has been located in the C-terminal PTK-like domain. The role of the second kinaselike domain is unknown.